Public knowledge of plastic-related chemical risks and intention to reduce exposure: a secondary analysis of an international randomized controlled trial - Danya Sandler; Rivka Green; Carly V. Goodman; Christine Till; Bruce Lanphear (BMC Public Health, 2026)
Abstract Background Endocrine-disrupting chemicals in plastics are linked to earlier puberty, adverse birth outcomes, and reduced cognitive function, yet public awareness of these risks remains low. We examined whether a brief educational video could increase knowledge about plastic-related hazards and intention to reduce plastic use. Methods This secondary analysis draws from a parallel-group randomized controlled trial [1] in which 15 761 participants aged 18–45 were recruited from Canada, the United States, the United Kingdom, India, and Australia via CloudResearch’s Prime Panels ® . After completing baseline demographic and knowledge measures, participants were randomly assigned to watch a 7-minute educational video about toxic chemicals and neurodevelopment ( n = 9135) or to briefly view a blank screen ( n = 6626). Immediate outcomes included three plastic-related knowledge items and one behavioural intention item assessing their likelihood of reducing plastic use in the next month. Following exclusions, 12 818 participants were included in analyses (intervention: n = 6427; control: n = 6391). Six weeks later, 3879 participants completed a follow-up assessing prevention attitudes and self-reported behaviour change. Results Participants who viewed the video were significantly more likely to report that plastics are harmful, disrupt hormone activity, and affect children’s cognitive development (rank-biserial r = .34–0.38, all p < .001). They also reported greater intention to reduce plastic compared with controls (51% vs. 44.8%, rank-biserial r = .06, p < .001). Intention was most strongly predicted by the belief that plastic chemicals disrupt hormone activity (OR = 1.99, p < .001). At six-week follow-up, higher baseline intention predicted greater self-reported reductions in plastic use (OR = 1.56, p < .001), with no significant difference by group. Effects varied across demographic subgroups, with stronger responses among participants in India, urban residents, South Asian participants, those with higher education or fewer children, and right-leaning participants. Conclusions A brief educational video improved plastics-related knowledge and short-term intentions to reduce exposure. However, behaviour change at follow-up was more strongly associated with baseline intention than with intervention status, highlighting the role of motivation and contextual factors in sustained behaviour change. Future interventions should consider baseline motivation and structural barriers alongside educational content.